Concurrent Acute Myeloid Leukemia and Autoimmune Hemolytic Anemia: Management Challenges and Clinical Insights: A Rare Case Report - Mais Musleh; Qossay Alhusein (Clinical Case Reports)
ABSTRACT The simultaneous occurrence of acute myeloid leukemia (AML) and autoimmune hemolytic anemia (AIHA) is exceedingly rare, with an incidence of less than 1%. We report the case of a 50–year–old patient newly diagnosed with this uncommon combination. This case underscores the complexity and infrequency of this dual diagnosis, highlighting the diagnostic and therapeutic challenges it presents.